The European Qualifications Framework and the European Lifelong Learning Perspective : how European countries are preparing to cope with the new philosophy of VET - Deissinger, Thomas [Verfasser] (My University, 2009)
"The paper picks up 'matching problems' related to current European education policy moves by referring to the German, the French and the Austrian VET system respectively. As we here refer to 'dual systems' or 'school-based systems' respectively, the pre-conditions for transforming European policy into national policies are very different. One major aspect here is the institutiona framework and the progression pathways from VET to higher education. European ideas accompanying the present 'Lisbon-Brugge-Copenhagen Process' demanding the opening-up of education and VET in the context of concepts such as the 'Learning Economy' or 'Lifelong Learning' have become a crucial background for re-framing the education system more or less fundamentally. VET systems with a strong focus on initial training obviously face the most serious challenges. Solutions lie in 'nation-specific' strategies which encourage and enable change without losing the benefits and the functionality of the established system. Austria and France seem more prepared than Germany when it comes to linking up VET and higher education through so-called 'hybrid qualifications'." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.1 Deutschland; I 2.2.1 Westeuropa; EU-Bildungspolitik; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Hochschulzugang; Fallstudie; Bundesrepublik Deutschland; Frankreich; Österreich